Primary subtalar arthrodesis in the treatment of comminuted calcaneal fractures: a functional and quality of life analysis - Nascimento Lawall, Ana Raquel; Soares Martins, Jefferson; Machado da Silva, Bruno Air; Freire de Moura Júnior, Ademir; Miguel da Silva, Mário Henrique; Ferreira Magalhães, Weverton; Pinheiro Lima, Daniel; Moreira Oliveira, Anderson Cleyton; de Figueiredo Rodrigues, Gabriella; Vieira Rocha, Rafael (Journal of the Foot & Ankle, 2022)
Objective: To survey literature findings on primary arthrodesis in Sanders type III and IV fractures and analyze functional and quality of life outcomes in patients submitted to this initial surgical procedure. Methods: This study described the profile of 12 patients diagnosed with severe comminuted intra-articular calcaneal fractures of Sanders type III and IV operated by a foot and ankle team. Patients attended from January 2016 to August 2021 with pre-/postoperative follow-up and application of the Orthopedic Foot and Ankle Score (AOFAS) questionnaire and Short Form Health Survey 36 (SF-36) quality of life questionnaire, along with clinical evaluation, were included. Data search was performed using the following online databases: PUBMED, MEDLINE, LILACS, and SCIENCE. Results: Most patients had a good range of motion, a mean AOFAS score of 81.71 points, and high mean scores in the domains physical functioning (84.44 points), role-physical (5.55 points), bodily pain (23 points), and general health (96.11 points) according to the SF-36 questionnaire. In general, there was bone consolidation after primary arthrodesis of the subtalar joint, and the functional status of patients was satisfactory. Conclusion: Primary arthrodesis is a relevant choice in fractures with more than three fragments, with a better postoperative outcome, including pain and maintenance of the hindfoot axis. Larger studies should be performed to assess more results of primary arthrodesis as a first treatment option for Sanders type III and IV fractures. Level of Evidence IV; Therapeutic Study; Case Series.